(3RGjQLI aj Yde GdMQha hGdChaGbs - (3eMeO Hf Rjf GdMQjQjs
(3ChdgG (B:s
(3PcQ Gfg QCi GdfHj Udi Gddg Ydjg hSe aj GdefGe s
(3BNQgG (B:s
(3jNQL dc GdLhGH eXhekG ceG CQOJ hGddg SHMGfg hJYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B36s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH s
Keywords: (3GdMQha h GdChaGbs